The Determinant Factors of Employee Job Satisfaction: Work-Life Balance, Engagement, and Commitment - Noviarani, Khurin In; Suyono, Joko; Irmawati, Irmawati; Elisabeth, Damarsari Ratnasahara; Sukaris, Sukaris (Universitas Muhammadiyah Gresik, 2025)
The purpose of this study is to analyze the influence of work-life balance, employee engagement, and organizational commitment on job satisfaction among employees of Badan Perencanaan Pembangunan, Penelitian Dan Pengembangan Daerah Kabupaten Gresik. The sample in this study consists of all 44 employees of Badan Perencanaan Pembangunan, Penelitian Dan Pengembangan Daerah Kabupaten Gresik. The data collection technique used was a questionnaire, while the data analysis technique employed multiple linear regression. The results of the study prove that work-life balance, employee engagement, and organizational commitment have both partial and simultaneous effects on job satisfaction among employees of Badan Perencanaan Pembangunan, Penelitian Dan Pengembangan Daerah Kabupaten Gresik. Among these three variables, employee engagement is found to have the dominant influence on job satisfaction among employees of Badan Perencanaan Pembangunan, Penelitian Dan Pengembangan Daerah Kabupaten Gresik.